Nanostructured tin oxide: synthesis and gas-sensing properties - Niranjan, R. S.; Hwang, Young Kyu; Kim, D. K.; Jhung, S. H.; Chang, J. S.; Mulla, Imtiaz S. (Materials Chemistry and Physics, 2005)
Pure and Ru-doped nanostructured SnO2 sensing materials were synthesized using a modified Pechini route. Incorporation of Ru in SnO2 results in the reduction of particle size (8.3 nm) compared with that of the pure SnO2 (28.2 nm). Moreover, the sensor exhibited a reasonably good sensitivity towards both H-2 and liquified petroleum gas (LPG). The effect of Ru incorporation, operating temperature, and gas concentration on the structure, morphology, and sensitivity is discussed using the results of X-ray diffraction (XRD), and scanning electron microscopy (SEM) along with sensing performance. © 2005 Elsevier B.V. All rights reserved.
Keywords: hydrogen and hydrocarbon sensor; Nanostructure; ruthenium; tin oxide

Synthesis of oleic acid capped copper nano-particles via reduction of copper salt by SFS - Khanna, P. K.; Kale, Trupti S.; Shaikh, Mushtaq; Rao, N. Koteswar; Satyanarayana, C. V. V. (Materials Chemistry and Physics, 2008)
Synthesis of oleic acid capped copper nano-particles has been carried out by use of sodium formaldehyde sulfoxylate (SFS) in aqueous medium. Nano-copper can be effectively coated with polyvinyl alcohol (PVA). Phase-pure nano-Cu can be obtained when water/acetone was used as aqueous medium. It is observed that the surface plasmon resonance (SPR) phenomena can be controlled during synthesis by the use of suitable reagent system, e.g. absorption band in presence of PVA can be blue shifted. As-prepared copper nano-particles were characterized by X-ray diffraction measurements (XRD), Scanning electron microscopy (SEM), energy dispersive analysis of X-rays (EDAX), thermo gravimetric analysis (TGA) and Fourier transform infra-red spectroscopy (FTIR). XRD analysis revealed broad pattern for fcc crystal structure of copper metal. The particle size by use of Scherrer's equation was calculated to be about 20 nm. TGA revealed similar to 10% weight loss due to the presence of surfactant. FTIR spectroscopy confirmed the presence of oleic acid around the particles. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Chemical synthesis; electronic materials; metals; Nanostructure

Y-junction nanostructures of palladium: enhanced electrocatalytic properties for fuel cell reactions - Subhramannia, Mahima; Ramaiyan, Kannan; Aslam, Mohammed; Pillai, Vijayamohanan K. (Journal of Electroanalytical Chemistry, 2009)
Here we demonstrate the utility of hierarchically designed alumina templates for the formation of palladium Y-junction nanostructures through a chemical vapor deposition route. These structures exhibit enhanced electrocatalytic activity for the oxidation of formic acid (up to 1020%) compared to that of platinum Y-junction nanostructures, which could be of immense relevance to portable fuel cell technology, since designing a better electrocatalyst for fuel cell reactions continues to be an important challenge. Apart from the obvious applications in fuel cell electrocatalysis, these Y-junction nanostructures could also act as promising candidates for room temperature hydrogen separation and more importantly as interconnects in molecular scale electronic devices. The present method of fabrication of Y-junction nanostructures using hierarchical alumina templates could be extended to other metallic/semiconducting systems facilitating more general opportunities for such hierarchical designs in nanoelectronics. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: electrocatalysts; fuel cells; Hierarchical structures; Nanostructure; Porous alumina membrane; Y-junctions

Nanostructure oxygen carrier used in chemical looping combustion process-A review - Badadare, Mansing M.; Adbale, Naina M.; Khomane, Ramdas B.; Kale, Ganesh R. (Advanced Science Letters, 2016)
Chemical looping combustion (CLC) is an emerging technology with inherent separation of CO2 from combustion of fuels. In this technique contact of air and fuel for combustion is restricted by providing oxygen through oxygen carrier (DC). The functional efficiency of CLC process mainly depends on the ability of oxygen carrier and it's reactivity, which undergoes repeated oxidation and reduction cycles. Nanostructure metal oxides have shown great potential application in the field of chemical looping combustion due to their high surface to volume ratio and enhanced structural properties. Synthesis technique of nanostructure metal oxides, their role as oxygen carrier, their reactivity with fuels along with their structural stability are reviewed herein. The contribution of various operating conditions on nanostructure oxygen carrier are considered in this review. These operating conditions and synthesis routes are summarized and classified according to metal oxides.
Keywords: Chemical looping combustion; CO2 Emission; Metal Oxide; Nanostructure; Oxygen Carrier

Ligand-free one-pot synthesis of Ru/W18O49 self-assembled hierarchical coral-like nanostructures for selective conversion of glucose into glycols - Patil, Manoj Krishnat; Gaikwad, Supriya Hanmant; Kirali, Arun Arunima Balachandran; Marimuthu, Banu; Mukherjee, Shatabdi Porel (ACS Applied Nano Materials, 2023)
In this study, we report a simple inorganic route for the synthesis of Ru/W18O49 self-assembled coral-like nanostructures, with the following advantages: It is one step and requires no surfactant or stabilizing agent; Ru loading is easily tuned, and the as-synthesized nanomaterials can be used as a catalyst without any further processing. The preliminary investigations of the catalytic performance of these as-synthesized Ru/W18O49 nanomaterials appear quite promising for converting glucose to glycols. The total glycol selectivity of 82.6% with 100% conversion of glucose was obtained over 0.03 wt % Ru loading on tungsten nanostructures, which turns out to be the lowest Ru loading% on support reported to date to achieve the highest total glycol selectivity among the previously reported catalyst based on Ru-nano/composite materials. Additionally, preliminary results show that the concentration of Ru on W18O49 significantly affects the selectivity of the glycol production. Thus, our methodology will open up a wide range of opportunities regarding the choice of metals, stoichiometric/nonstoichiometric WOx (x=1-3) as support, and the viability of further catalytic manipulations. A probable catalytic mechanism for this catalytic process is also proposed.
Keywords: glycols; Nanostructure; One-pot synthesis; ruthenium (Ru); selective conversion of glucose; tungsten oxide (W18O49)